PSYCHOLOGICAL AND PEDAGOGICAL SUPPORT OF STUDENTS WITH HEARING IMPAIRMENT IN CONDITIONS OF INCLUSIVE EDUCATION - O. Solovieva; O. Simonenko (Вестник Северо-Кавказского федерального университета)
The article presents the results of an experimental study on the introduction of psychological and pedagogical support for adolescent schoolchildren with hearing impairment in an inclusive educational environment. The high relevance of this study is substantiated, the degree of its elaboration and brief theoretical foundations are shown. It is emphasized that psychological and pedagogical support is a polysystemic process, the effectiveness of which is achieved by the coordinated work of the participants of an interdisciplinary team. The content of the program of psychological and pedagogical support and the conditions under which its implementation will be effective are described. The results of this experimental study are analyzed and its prospects are indicated.